Regional Development Policy Strategies for Strengthening the Social and Economic Resilience of Local Communities Under the New Development Paradigm - Suaib; Nur Ichsan Amin; Sultan; Irwan (Lembaga Bale Literasi, 2026)
This study aims to analyze regional development policy strategies as implications in the new paradigm of social and economic resilience of local communities. The research is motivated by the still occurrence of regional development inequality, low community participation in the development process, and weak local economic strengthening in rural areas. The research uses a qualitative approach with a case study type to understand in depth the dynamics of regional development policies and the experiences of local communities in maintaining socio-economic resilience. Data collection was carried out through semi-structured interviews, participatory observations, and documentation of local government officials, community leaders, local business actors, farmers, and fishermen who were selected using purposive and snowball sampling techniques. The results of the study show that regional development is still dominated by the physical development approach rather than strengthening the economic capacity of the community. Community participation in the development process is still formalistic and not fully substantive. On the other hand, local communities have strong social capital through the practice of mutual cooperation, social solidarity, and community cooperation which play an important role in maintaining the socio-economic resilience of the community. This study also found that limited access to capital, weak distribution infrastructure, and lack of business assistance are the main obstacles to local economic development. This research contributes to the development of sociological studies of development and regional development, especially related to the relationship between development policies, social capital, and the economic resilience of local communities. Practically, this study recommends strengthening participatory development based on local potential through increasing community economic access, strengthening local institutions, and developing more inclusive and sustainable policies